2015
DOI: 10.1097/pap.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Intratubular Germ Cell Neoplasia of the Testis

Abstract: Germ cell tumors of the testis may be divided into 3 broad categories according to age at presentation. The tumors in the pediatric age group include teratoma and yolk sac tumor. These tumors are generally not associated with convincing intratubular neoplasia. The second group consists of tumors presenting in third and fourth decade of life and include seminoma, embryonal carcinoma, yolk sac tumor, choriocarcinoma, and teratoma as well as mixed germ cell tumors. The precursor cell for these tumors is an abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…This progenitor shares many characteristics of a primordial germ cell (PGC)/ gonocyte, such as mRNA/miRNA/protein expression (including the coexpression of POU5F1 [also known as OCT3/4] and SOX17) (Looijenga et al 2003;de Jong et al 2008), as well as global CpG methylation erasure, features also found in invasive SE (Port et al 2005;Netto et al 2008;Wermann et al 2010;Al-Hussain et al 2015). However, while PGCs express multiple biomarkers of pluripotency shared with blastocyst inner cell mass stem cells, they are normally unipotent to produce gametogenic stem cells, and the spawning of differentiated somatic elements in this lineage is pathologic.…”
mentioning
confidence: 99%
“…This progenitor shares many characteristics of a primordial germ cell (PGC)/ gonocyte, such as mRNA/miRNA/protein expression (including the coexpression of POU5F1 [also known as OCT3/4] and SOX17) (Looijenga et al 2003;de Jong et al 2008), as well as global CpG methylation erasure, features also found in invasive SE (Port et al 2005;Netto et al 2008;Wermann et al 2010;Al-Hussain et al 2015). However, while PGCs express multiple biomarkers of pluripotency shared with blastocyst inner cell mass stem cells, they are normally unipotent to produce gametogenic stem cells, and the spawning of differentiated somatic elements in this lineage is pathologic.…”
mentioning
confidence: 99%
“…The different histologic types of type II GCT are intimately related. The precursor lesion of GCT, GCNIS, shares many phenotypical and morphologic features with seminoma, suggesting a precursor relationship [57][58][59]. However, molecular abnormalities more characteristic of other forms of invasive GCT, such as embryonal carcinoma (EC) or YST, can also be seen in GCNIS, suggesting that the in situ lesion may also play a role of precursor to other forms of GCT as well [57].…”
Section: Histogenesismentioning
confidence: 95%
“…Intratubular teratoma [86] and YST [87] have also been reported. Intratubular ST shows the three characteristic types of cells of the invasive counterpart (see below) and is always associated with an invasive component [58]. Metastatic carcinomas to the testis may show involvement of seminiferous tubules resembling GCNIS [88].…”
Section: Differential Diagnosismentioning
confidence: 98%
See 2 more Smart Citations